Dark microglia: A new phenotype predominantly associated with pathological states. Issue 5 (5th February 2016) - Bisht, Kanchan; Sharma, Kaushik P.; Lecours, Cynthia; Gabriela Sánchez, Maria; El Hajj, Hassan; Milior, Giampaolo; Olmos‐Alonso, Adrián; Gómez‐Nicola, Diego; Luheshi, Giamal; Vallières, Luc; Branchi, Igor; Maggi, Laura; et al.
Abstract : The past decade has witnessed a revolution in our understanding of microglia. These immune cells were shown to actively remodel neuronal circuits, leading to propose new pathogenic mechanisms. To study microglial implication in the loss of synapses, the best pathological correlate of cognitive decline across chronic stress, aging, and diseases, we recently conducted ultrastructural analyses. Our work uncovered the existence of a new microglial phenotype that is rarely present under steady state conditions, in hippocampus, cerebral cortex, amygdala, and hypothalamus, but becomes abundant during chronic stress, aging, fractalkine signaling deficiency (CX3 CR1 knockout mice), and Alzheimer's disease pathology (APP‐PS1 mice). Even though these cells display ultrastructural features of microglia, they are strikingly distinct from the other phenotypes described so far at the ultrastructural level. They exhibit several signs of oxidative stress, including a condensed, electron‐dense cytoplasm and nucleoplasm making them as "dark" as mitochondria, accompanied by a pronounced remodeling of their nuclear chromatin. Dark microglia appear to be much more active than the normal microglia, reaching for synaptic clefts, while extensively encircling axon terminals and dendritic spines with their highly ramified and thin processes. They stain for the myeloid cell markers IBA1 and GFP (in CX3 CR1‐GFP mice), and strongly express CD11b and microglia‐specific 4D4 in their processes encircling synaptic elements, and TREM2 when they associate with amyloid plaques. Overall, these findings suggest that dark microglia, a new phenotype that we identified based on their unique properties, could play a significant role in the pathological remodeling of neuronal circuits, especially at synapses. GLIA 2016;64:826–839 Main points: We describe a new microglial phenotype. These cells appear extremely active at the synapse and show signs of oxidative stress. They are abundant during chronic stress, aging, fractalkine signaling deficiency, and Alzheimer's disease pathology.